IMPROVING STUDENT LEARNING OUTCOMES IN PPKN SUBJECTS THROUGH JIGSAW LEARNING MODEL WITH CUBLAK SUWENG GAME - Awalia Maulidina Qotrunnada; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Civics learning is often boring for students. The purpose of this study was to determine the increase in student learning outcomes in fourth grade Civics subjects through the jigsaw learning model with the cublak suweng game. The subjects of this study were fourth grade students at SDN Mlajah 2 Bangkalan and class teachers. In this study, researchers used classroom action research consisting of 2 cycles with qualitative and quantitative approaches. Data collection techniques used are observation, interviews, tests and documentation. The results showed that the average pre-test score was 63.33 with a classification of 29.62%. The average in cycle I was 73.70 with classical completeness of 48.15% in the good category, the percentage of increasing student learning outcomes that were completed was 48.15%, the percentage of student activity was 67.5% in the good category and the teacher was 77.7%. in good category. In cycle II the average score was 86.11 with 96.30% classical completeness, the percentage of student activity was 85% in the very good category and the teacher was 94% in the very good category. The conclusion is that there is an increase in the learning outcomes of class IV UPTD SD Mlajah 2 Bangkalan in Civics lessons through the jigsaw type cooperative learning model with the cublak suweng game.